2022
DOI: 10.3389/fmed.2022.859555
|View full text |Cite
|
Sign up to set email alerts
|

Application of Muscle Thickness and Quality Measured by Ultrasound in Frailty Assessment in China

Abstract: To explore the correlation between Fried Frailty Phenotype (FFP) and the muscle thickness and quality of local muscle, and to provide a reasonable basis for the application of ultrasound measurement in the frailty assessment. A total of 150 people (age ≥ 65 years, 58 women, 92 men) were included from the First Hospital Affiliated to Nanjing Medical University. They were divided into Normal group (40 cases), Prefrailty group (69 cases) and Frailty group (41 cases). The thickness and the quality of local muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In contrast, the muscle thickness and echo intensity of the upper limb had no statistical significance. These results were consistent with previous studies [ 10 , 15 ], At the same time, based on the research of Canales et al [ 16 ], we found that the thickness and echo intensity of the vastus lateralis and tibialis anterior muscles were also closely related to the assessment of frailty. It provides more muscle choices for the follow-up research on sarcopenia and frailty.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, the muscle thickness and echo intensity of the upper limb had no statistical significance. These results were consistent with previous studies [ 10 , 15 ], At the same time, based on the research of Canales et al [ 16 ], we found that the thickness and echo intensity of the vastus lateralis and tibialis anterior muscles were also closely related to the assessment of frailty. It provides more muscle choices for the follow-up research on sarcopenia and frailty.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, muscle thickness, CSA, fascicle length, and PA, but not muscle stiffness, were found to be significantly lower in frail subjects compared to non-frail ones. In the previous studies, muscle thicknesses of thigh muscles were found to be related to frailty, as frail subjects had lower muscle thickness compared to normal and pre-frail individuals, which was consistent with our results [ 13 , 15 ]. On the other hand, apart from the current study, these studies evaluated more than one thigh muscles but measured only the thickness of muscles.…”
Section: Discussionsupporting
confidence: 93%
“…Rectus femoris muscle (RFM), a part of the quadriceps muscle group, is frequently evaluated in the literature to estimate skeletal muscle mass with high spatial ultrasound resolution and the highest intra- and inter-rater reliability [ 10 12 ]. The relation between ultrasonographic parameters of skeletal muscle and frailty among older people was scarcely investigated [ 13 , 14 ]. Shan et al reported that the thickness and quality of skeletal muscles of the lower extremities were affected by the frailty status [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults, muscle thickness showed high a correlation with appendicular FFM measured by DXA [138]. It has been proposed as a low-cost objective method for muscle evaluation in nutritional assessments [139,140].…”
Section: Standard Nutritional Ultrasound ® To Assess Malnutrition/sar...mentioning
confidence: 99%